2023
DOI: 10.15218/ejnm.2023.05
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Practices, and Attitudes of Nurses Regarding Non-Pharmacological Pain Management in the Midwifery Ward

Shahla Shareef,
Tiran Piro

Abstract: Background and Objectives: Pregnant women are frequently worried about labor pain, and it is usually the most important problem for them and their relatives. Non-pharmacological pain relief methods provide several benefits, such as no harmful effects on the fetus or baby, no interruption of labor, and even being pleasurable for the mother and fetus. The aim of this study was to assess the nurse’s knowledge, practice, and attitude toward non-pharmacological pain management methods in the delivery room in Erbil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, the procedures stated above disrupt labour pain management, requiring midwives to either wait for the doctor or follow phone instructions. Both Pethidine and Phenergan work effective in sedating and calming the woman, as well as reducing birth pains [ 16 , 17 , 24 , 25 ]. Like our study, other studies have reported the use of pethidine and Phenergan as analgesics in various African countries, which include Egypt [ 26 ], Ghana [ 27 ], Ethiopia [ 24 , 28 ], and Nigeria [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the procedures stated above disrupt labour pain management, requiring midwives to either wait for the doctor or follow phone instructions. Both Pethidine and Phenergan work effective in sedating and calming the woman, as well as reducing birth pains [ 16 , 17 , 24 , 25 ]. Like our study, other studies have reported the use of pethidine and Phenergan as analgesics in various African countries, which include Egypt [ 26 ], Ghana [ 27 ], Ethiopia [ 24 , 28 ], and Nigeria [ 29 ].…”
Section: Discussionmentioning
confidence: 99%